Consumptive coagulopathy is associated with a disturbed host response in patients with sepsis. (17th February 2021) - van Vught, Lonneke A.; Uhel, Fabrice; Ding, Chao; van't Veer, Cees; Scicluna, Brendon P.; Peters‐Sengers, Hessel; Klein Klouwenberg, Peter M. C.; Nürnberg, Peter; Cremer, Olaf L.; Schultz, Marcus J.; van der Poll, Tom; ,
Abstract: Background: A prolonged prothrombin time (PT) is a common feature in sepsis indicating consumptive coagulopathy. Objectives: To determine the association between a prolonged PT and aberrations in other host response mechanisms in sepsis. Methods: Patients admitted to the intensive care unit with sepsis were divided in quartiles according to the highest PT value measured within 24 h after admission. The host response was evaluated by measuring 19 plasma biomarkers reflecting pathways implicated in sepsis pathogenesis and by blood leukocyte gene expression profiling. Measurements and Main Results: Of 1524 admissions for sepsis, 386 (25.3%) involved patients with a normal PT (≤12.7 s); the remaining quartiles entailed 379 (24.9%) patients with a slightly prolonged PT (12.8 ≤ PT ≤ 15.0 s), 383 (25.1%) with an intermediately prolonged PT (15.1 ≤ PT ≤ 17.2 s), and 376 (24.7%) with an extremely prolonged PT (≥17.3 s). While patients with an extremely prolonged PT showed an increased crude mortality up to 1 year after admission, none of the prolonged PT groups was independently associated with 30‐day adjusted mortality. Comparison of the host response between patients with a normal PT or an extremely prolonged PT matched for baseline characteristics including severity of disease showed that an extremely prolonged PT was associated with impaired anticoagulant mechanisms, a more disturbed endothelial barrier integrity and increased systemic inflammation, and blood leukocyte transcriptomes indicating more prominent metabolic reprogramming and protein catabolism. Conclusion: A prolonged PT is associated with stronger anomalies in pathways implicated in the pathogenesis of sepsis, suggesting that activation of coagulation impacts other host response mechanisms.